Education as a Competitive Differentiator of the BRICS Countries - ZHILTSOVA, Svetlana Vladimirovna; AGIBALOVA, Elena Leonidovna; STUKALOVA, Irina Borisovna (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The article is dedicated to the analysis of the economic situation in countries with rapidly developing national economies: Russia, China, India, Brazil and South Africa that have a significant impact on regional and global markets. These countries could have become a dominant economic system thanks to rapid growth rate, powerful domestic markets and the use of innovations. The main question concerns the role of education as one of the decisive factors of global competitiveness formation both for the Russian and the BRICS economies. The BRICS governments made education the core of their strategic development allocating considerable investments for the creation of competitive higher education institutions and research institutes. The overview of the educational systems in Russia, China, India and South Africa makes it possible to single out main similarities and differences in management in the sphere of education and determine main trends aimed at the convergence of educational systems. Internationalization of higher education is one of the considerable factors of the formation of competitiveness among higher education institutions amid transformation of the global educational market and the role of the BRICS countries can significantly influence the change in the number of students receiving higher education abroad. It all results in the changes in the management system and the elaboration of recognizable educational standards. Russia, having considerable experience and level of education, could have played an important part in this process. One of the main indicators of competitiveness of educational institutions are international rankings which have evaluated positions of BRICS leading educational institutions (QS) separately as independent and important members of the global educational space.
Keywords: competitiveness; education; education management; educational system; education in BRICS countries; internationalization of education; student mobility; international rating institutions